Opposite effect of basic combat training on mood state of recruits with different physical fitness: A study from perspective of fatigue - Ruan, Yi; Song, Shang-jin; Yin, Zi-fei; Wang, Xin; Zou, Bin; Wang, Huan; Gu, Wei; Ling, Chang-quan (Frontiers in Psychology, 2022)
Objective: Basic combat training (BCT) is a kind of necessary high-intensity training to help each military recruit convert into a qualified soldier. In China, both the physical fatigue and passive psychological state have been observed in new recruits during BCT. However, after same-intensity training, the degree of fatigue and passive mood vary among recruits. Therefore, this study aimed to explore the effect of BCT on mood state of recruits with different physical fitness levels from a perspective of fatigue. Method: Before and after BCT, the degree of fatigue and mood state of participants were evaluated via the Borg Rating of Perceived Exertion Scale and Profile of Mood States Questionnaire immediately after 20 push-ups as RPE and POMS scores (total mood disturbance [TMD], passive mood [T-tension, T-anger, T-fatigue, T-depression, and T-confusion] and positive mood [T-vigour and T-esteem]). The participants were divided into two groups according to the RPE score measured after BCT: (1) group 1: RPE score after BCT < 13 and (2) group 2: RPE score after BCT ≥ 13. Result: A total of 564 recruits were included (group 1: 456/564, 80.85%; group 2: 108/564, 19.15%). After BCT, in group 1, TMD (from 95.65 ± 17.89 to 87.52 ± 17.63) and passive mood T-tension (from 4.46 ± 3.18 to 3.79 ± 3.14), T-fatigue (from 4.94 ± 3.58 to 3.12 ± 3.04), T-depression (from 2.86 ± 3.41 to 2.01 ± 2.75), T-confusion (3.12 ± 2.72 to 2.42 ± 2.57) declined significantly (all within-group p < 0.001), but positive mood both increased significantly (T-vigour: from 13.21 ± 4.59 to 15.44 ± 5.42, T-esteem: from 9.18 ± 3.36 to 11.04 ± 3.67; both within-group p < 0.001); while in group 2, only T-anger (from 4.27 ± 4.16 to 6.22 ± 5.94, within-group p = 0.001) and T-esteem (from 8.36 ± 3.15 to 9.07 ± 3.67, within-group p = 0.031) increased significantly. Conclusion: BCT could alleviate passive mood and add to positive mood for recruits with better physical fitness, while had no ameliorative effects on or even deteriorate most of the passive mood for recruits with worse physical fitness.